Effect of Adenine Nucleotides on Levels of Glycolytic Intermediates during the Development of Induced Respiration in Carrot Root Slices - Adams, P. B. (1970)
Incubation of freshly cut carrot tissue in Na(3)ADP and Na(3)ATP promotes a marked intracellular increase in both ADP and ATP. The rapid increase in ATP during an ADP incubation and in ADP during an ATP incubation results from the activity of cytoplasmic enzyme systems upon the nucleotide absorbed into the cell from the incubation medium. There is a crossover at the pyruvate kinase reaction, but not at phosphofructokinase, when either ADP or ATP is added to freshly cut tissue. In tissue slices washed in distilled water, pyruvate kinase exhibits a negative crossover in the first 2 hours and a positive crossover between 2 and 10 hours after cutting. Cutting induces large changes in levels of nucleotides and glycolytic intermediates. There is an immediate depletion of these compounds upon cutting, so that nucleotides are added to a system where respiration rate is limited by endogenous nucleotide level. Variation in respiratory values for fresh cut tissue can be explained in terms of a range of endogenous ADP levels in different tissue batches. Nucleotide incubation experiments are discussed in relation to the provision of ADP to rate-limiting pyruvate kinase during the first phase in development of the induced respiration.